2015
DOI: 10.1080/16864360.2015.1059202
|View full text |Cite
|
Sign up to set email alerts
|

Embodied prototyping: exploration of a design-fabrication framework for large-scale model manufacturing

Abstract: For designers of large products such as boats, cars and houses, there have been few cost-effective machines or methods in support of one-to-one, large-scale physical prototyping. A novel physical production system is demonstrated, aiming at rapid prototyping of large-scale models. Research questions address possible ways that the system can support design prototyping as opposed to manufacturing. We present computational methods used to generate model data, principle of decomposition of a large model, and assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
0
4
0
2
Order By: Relevance
“…obtained by printing the final geometry in parts to be successively re-assembled. Accordingly, Sass et al (2016) recently suggested a procedure for obtaining large 3D prototypes from 2D-cut parts. However, these kinds of models are characterized by low geometrical accuracy, due to the highly discontinued profiles that can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…obtained by printing the final geometry in parts to be successively re-assembled. Accordingly, Sass et al (2016) recently suggested a procedure for obtaining large 3D prototypes from 2D-cut parts. However, these kinds of models are characterized by low geometrical accuracy, due to the highly discontinued profiles that can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, origamic architecture papercrafts [LLLN* 13], iris papercrafts [IIM16] or animated pop‐ups that show motions of articulated characters [RLL15] are available. Such approaches have been investigated for large‐scale models [SCS16, CS17], as well as for entire 3D scenes through developable surfaces [PDRK18], and the automatic generation of paper architecture [LSH* 10]. None of these approaches looks into generating physical models from volumetric data (only from mesh data), while they only employ paper.…”
Section: Related Workmentioning
confidence: 99%
“…Producing large artifacts from small footprint or low-cost digital fabrication machines, such as laser cutters and 3D printers have been investigated in the past (Sass 2004;Dritsas & Kashyap 2005;Sass et al 2015). Our contributions are in the integration of geometric modeling, analysis and optimization procedures in a nearly instant connection of upstream design and downstream production considerations aiming to be accessible to non-technical audiences.…”
Section: Introductionmentioning
confidence: 99%